STRATEGI PENGEMBANGAN SUB TERMINAL AGRIBISNIS REJANG LEBONG - Meza Yolanda; Dodi Aprianto; Fitri Lestari (Jurnal Riset Rumpun Ilmu Tanaman, 2022)
Research on Strategy Development of Rejang Lebong Agribusiness Sub Terminal, aims to analyze internal and external factors of Agribusiness Sub Terminal in Rejang Lebong Regency in order to keep growing and formulate alternative strategies for Agribusiness Sub Terminal development in Rejang Lebong Regency. This research was conducted in March 2022 in Simpang Nangka Village, Selupu Rejang District, Rejang Lebong Regency. The data analysis method used in this research is strategy formulation analysis consisting of internal and external factor analysis, internal external matrix analysis, Strength, Weakness, Opportunity, And Threat (SWOT) analysis, and analytic hierarchy process (AHP). The results of this study indicate that the internal factors consisting of strengths and weaknesses that have the highest value are relatively large agricultural/plantation lands. External factors consisting of opportunities and threats that have the highest score are the availability of superior and potential commodities (vegetables, fruit, coffee, grain/rice, and corn) which are very large both nationally, regionally and internationally. This can be strengthened by the AHP decision-making method where the level of the factor that becomes the main priority in achieving the strategic focus of developing the Rejang Lebong agribusiness sub-terminal is the HR factor.